(untitled) (Global Journal of Medical Research, 2016)
Background: Central neurogenic hyperventilation (CNH) is a rare but well documented complication after endoscopic third ventriculostomy (ETV) in adults. Case Characteristics: 6 year old developed CNH, acute respiratory alkalosis, intraoperative tachycardia and lactic acidosis following ETV for a pineal gland tumour causing obstructive hydrocephalus. Observations: Attributed to irritation of the hypothalamus while irrigating the floor of the thrid ventricle with normal saline. Outcome: Treatment with sedation and oxygen via rebreathing mask resulted in normalization of symptoms and blood gas. Message: CNH can occur in children following ETV and should be recognized early. Measurement of ICP during ETV and use of alternative irrigation fluids such as lactated ringer’s or artificial CSF may minimize occurrence.